Exploring the potential of naturally-derived ionic liquids for sustainable vegetable oil deacidification - Farias, Fabiane O.; Toledo Hijo, Ariel A.C.; Mussagy, Cassamo U.; Ferreira, Ramon S.B.; Santos-Ebinuma, Valeria C. [UNESP]; Batista, Eduardo A.C.; Meirelles, Antonio J.A. (Elsevier, 2023)
This work investigated two different approaches for vegetable oil deacidification using an ionic liquid (IL), composed of cholinium cation ([Ch]) and oleate anion ([OLE]), as a solvent to form oligomeric ILs (OILs) potentially, and reactive extraction to form multicomponent ILs (MILs) from different acids. The OIL approach (adding an excess acid into the IL through hydrogen bonding) removed oleic acid (∼80%) from a commercial vegetable soybean oil, previously acidified, possibly due to high intermolecular interactions. Through MIL approach, the FFA removal was up to 85%. In this case, the MIL formation occurred concomitant to deacidification as a driving force. Both strategies were evaluated in crude vegetable oil, and the high removal indexes were maintained. Concerning the oil loss, the MIL and OIL approaches result in a significantly lower oil loss (up to 5%) than conventional chemical processes (up to 50%). Finally, envisioning integrated processes, MIL was reused in a new deacidification process, achieving good results (removal of FFA up to 85%). Alternatively, reused MILs and OILs were employed in the β-carotene and astaxanthin recovery from P. rhodozyma wet biomass, indicating that the obtained IL-based systems could be further used as green solvents for other sustainable extraction processes.
Keywords: Choline; Fatty acids; Integrative processes; Multicomponent ionic liquids; Oligomeric ionic liquids